Public Finance in Developing Countries - Prest, A.R.P. (London Weidenfeld and Nicolson, 1975)
This book is based on a series of seven lectures delivered at the Centro de Estudo de Estatistica Economica, Lisbon, in April 1961.
Includes bibliography, index
osc 23/5/17
Loans
Keywords: Public Finance; Finance